The Present State of Probation in Legal Sector (Revista da Faculdade de Direito, Universidade de São Paulo, 2006)
Many internships of Law students are misrepresented, because full-time employment relationships are deceptively represented as internships. A field research project was conducted, involving 1,050 law students from public and privates colleges. The students answered a questionnaire about internships in the field of law. The purpose of this study is to demonstrate the negative consequences of this practice of misrepresentation.